2016
DOI: 10.1161/circoutcomes.116.003041
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Teamwork in Cardiovascular Care Outcomes

Abstract: Background The nature of teamwork in healthcare is complex and interdisciplinary, and provider collaboration based on shared patient encounters is crucial to its success. Characterizing the intensity of working relationships with risk adjusted patient outcomes supplies insight into provider interactions in a hospital environment. Methods and Results We extracted four years of patient, provider, and activity data for encounters in an inpatient cardiology unit from Northwestern Medicine’s Enterprise Data Wareh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…We identified two approaches to defining how many shared patients "counted" as a connection between two providers. One approach used a fixed threshold of shared patients (e.g., 1, 2, 5 shared patients) [23][24][25][26][27]. A second approach used relative thresholds.…”
Section: Network Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified two approaches to defining how many shared patients "counted" as a connection between two providers. One approach used a fixed threshold of shared patients (e.g., 1, 2, 5 shared patients) [23][24][25][26][27]. A second approach used relative thresholds.…”
Section: Network Constructionmentioning
confidence: 99%
“…Nonpatient facing physicians such as anesthesiologists, emergency medicine, radiologists, and pathologists were excluded in 11 studies [14,[28][29][30][31][32][33][34][35][36][37]. Studies also varied in geographic scope, ranging from constructing networks by country [20,38,39], hospital referral region [26,28,30,34,40], state [16,21,31,41], city [42,43], or within a hospital or health system [24,25,29,[44][45][46][47][48][49]. The geographic boundaries of a network are important to consider because networks are subject to the boundary specification problem in which excluding certain patients and/or providers may alter the network structure [50].…”
Section: Network Constructionmentioning
confidence: 99%
“…A modified SNA approach with community detection algorithms [2628] has been developed to assess physicians’ characteristics in the network and within smaller communities (i.e., sub-dividing a large care network into smaller groups of nodes more densely connected). Using this approach, they showed that patients whose physicians were connected with larger number of physicians had higher spending.…”
Section: Introductionmentioning
confidence: 99%
“…The SPOR measurement is a pairwise metric that quantifies the ratio of specific positive outcomes shared between two providers versus outcomes shared with other providers, which is defined in more detail in past studies. 17,18 We built a provider collaboration network and calculated the SPOR edge weight. Two providers were linked within the network if each logged activity into the EHR for the same patient encounter between February 1, 2015 and January 31, 2016.…”
Section: Shared Positive Outcome Ratiomentioning
confidence: 99%
“…A method for quantifying the connections or edges between providers in a network, through their shared encounters, has been previously developed: the Shared Positive Outcome Ratio (SPOR). 17,18 The SPOR is a pairwise metric that quantifies the ratio of positive patient outcomes shared between two providers, versus all the positive patient outcomes when each of those two providers works with others in the network. This measure could be used in quality improvement processes; however, to be reliable we need to understand the role risk adjustment plays in the measure.…”
Section: Introductionmentioning
confidence: 99%